THE INFLUENCE OF INTELLECTUAL CAPITAL AND SHARIA FINANCIAL LITERACY ON FINANCIAL BEHAVIOR IN PAREPARE CITY MSMEs - Tamara, Ainun; Muhammadun, Muzdalifah; Andi Ayu Frihatni (Islamic Financial And Accounting Review, 2023)
This research aims to determine the influence of Intellectual Capital and Sharia Financial Literacy on Financial Behavior in Parepare City MSMEs, both partially and simultaneously. This research uses quantitative research methods with an associative approach and field research. The data collection technique used was observation and distribution of questionnaires to 100 Parepare City MSMEs as samples in this research. The data processing technique uses the SPSS version 25 application with research instrument testing, classical assumption testing, and hypothesis testing. The results of the research that has been carried out are partial, the two independent variables, namely Intellectual Capital and Sharia Financial Literacy, both have a significant influence on the dependent variable, namely Financial Behavior. Likewise, simultaneously, Intellectual Capital and Sharia Financial Literacy have a significant effect on Financial Behavior.